2013
DOI: 10.1136/neurintsurg-2013-010756.rep
|View full text |Cite
|
Sign up to set email alerts
|

Intraprocedural parenchymal blood volume as a marker of reperfusion status in acute ischemic stroke intervention

Abstract: Parenchymal blood volume (PBV) mapping with flat panel detectors may provide real-time estimates of tissue perfusion during endovascular ischemic stroke procedures. We present two cases of acute middle cerebral artery (MCA) occlusion to demonstrate how PBV may: (1) be used in acute stroke; (2) influence intraprocedural decision-making; and (3) potentially serve as a predicator of clinical outcome. Both cases were successfully recanalized with endovascular embolectomy. Intraprocedural PBV maps were obtained imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…PBV map and CTP-CBV/MRP-CBV have good consistency in terms of both visual comparison of perfusion pseudo-color maps and the quantitative analysis of ROI ( 26 , 29 , 30 , 50 , 51 ). In addition to PBV's application in AIS evaluation ( 24 26 , 28 ) and initial practice in the prediction of DCI after aneurysmal SAH ( 23 , 30 ), our study broadens the clinical application of PBV in stroke management.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…PBV map and CTP-CBV/MRP-CBV have good consistency in terms of both visual comparison of perfusion pseudo-color maps and the quantitative analysis of ROI ( 26 , 29 , 30 , 50 , 51 ). In addition to PBV's application in AIS evaluation ( 24 26 , 28 ) and initial practice in the prediction of DCI after aneurysmal SAH ( 23 , 30 ), our study broadens the clinical application of PBV in stroke management.…”
Section: Discussionmentioning
confidence: 92%
“…The reliability of PBV maps was demonstrated by the good correlation between PBV and conventional CT perfusion through both qualitative and quantitative comparative studies (29,33,41). By extending the imaging capabilities of the angio-suite, the PBV technique has been used in the assessment of ischemic cerebrovascular diseases and brain tumors in the brain during the procedure in the angio-suite for better patient management, and has gained significant value in clinical practice in recent years (24)(25)(26)(27)(28)42) but not much value in SAH yet. Our study demonstrated PBV's feasibility in assessing the perfusion status in aneurysmal SAH, as well as the convenience of one-stop imaging evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations